Mobile Radio Streaming Application Using Networked Radio System as a Media Convergence Collaboration Movement for Ponorogo Radio Discussion Forum - Mochammad Iqbal Pristiyo; Dihin Muriyatmoko; Nur Aini Shofiya Asy'ari (Universitas Muhammadiyah Sidoarjo, 2021)
The development of streaming radio has been very developed, radio in digital form is also known as internet radio because to access streaming radio you must use the internet media. However, there are several radio stations in Ponorogo that still use conventional radio whose coverage is limited because they use an antenna to reach the signal range, and can only reach local areas because Ponorogo has several highlands and several mountains. This study aims to create a Networked Streaming Radio application so that Ponorogo radio station broadcasts can reach any place that has an internet connection and can accommodate the Ponorogo radio station industry which still does not have an Android-based streaming radio as a media convergence collaboration movement for the Ponorogo radio discussion forum. This research uses the waterfall which consists of five stages, namely: identification, design, implementation, verification, maintenance. Testing this streaming radio application using the black box method shows the application is running well and there are no errors. Testing using 6 different media and resolutions was carried out to find out whether the Ponorogo Radio application could run well on various media/smartphones and different resolutions.